Representasi Prasangka dan KeserakahanDalam Mencapai Tujuan Pribadi (Analisis Semiotika FilmParasite, 2019). - Lia Rahmawati, (2020)
Parasite, is a film that stole the attention of audiences in 2019, the film is from South Korea, directed by Bong Joon-Hoo, is a satirical comedy. It tells the story of a poor family (Mr. Kim) and a rich family (Mr. Park) and the interpersonal relationships that exist between them. The interpersonal relationships that exist between them, are built on greed and prejudice. The interpersonal relationships that are based on greed and prejudice ultimately help the Kim Family achieve their goals. The researcher uses Roland Barthes's semiotics theory as the foundation in conducting the analysis in this study. Researchers analyze the scene by scene in Parasite Films and try to categorize whether the scene is included in the concepts of greed and prejudice in relation to building interpersonal relationships between the two. Researchers also conducted interviews with film semiotics experts, to strengthen the results of the analysis that researchers had done. The film Parasite teaches many things and in this study, the researcher wants to convey the learning about how to build interpersonal relationships with other people, so that finally a person can achieve his personal goals. Key words : Parasite, Interpersonal realtionships, Semiotics, Prejudice, Greed.